The Health Extension Program: A flagship for bringing health services to the doors of communities - Mekbib, Tekle-Ab (Ethiopian Journal of Reproductive Health, 2018)
Abstract Recognizing the need for strengthening the health care delivery system in the country, and to bring services to the doors of communities, the Government of Ethiopia has launched the Health Extension Program (HEP). HEP is a new initiative developed as one of the components of the Health Sector Development Program (HSDP-II), which is an innovative community based health care delivery system. In order to address the acute shortage of human resources in the areas of health, and the prevailing constraints in the training of health professionals, HEP has also become a centerpiece for the “Accelerated expansion of primary health care coverage” program. Under HEP, in the coming two years, over 30,000 health extension workers (HEWs) will be trained and deployed for some 15,000 health posts, which includes the construction and/or upgrading of 3153 health centers. The main objective of HEP is to improve access and equity to preventive essential health interventions provided at village and household levels with focus on sustained preventive health actions and increased health awareness. It also serves as effective mechanism for shifting health care resources from being dominantly urban to the rural areas where the majority of the country’s population resides. The Government has now trained and deployed close to 17,500 HEWs, and they were assigned to about 9000 health posts (villages), and this comprises over 60% of the planned 33,200 HEWs to have blanket coverage. HEP is considered as the most important institutional framework for achieving the Millennium Development Goals. (Ethiop. J. Reprod. Health May 2007, 1 (1), 75-85)